The social organization of the Gilyak. Anthropological papers of the AMNH - Shternberg, Lev I︠A︡kovlevich, 1861-1927.; Grant, Bruce, 1964- ([New York] : American Museum of Natural History, 1999)
lvi, 280 p. : ill. (some col.), maps 26 cm. Includes bibliographical references (p. 256-272) and index.